The rational believer: choices and decisions in the madrasas of Pakistan - Bano, Masooda (Cornell Univ. Press, 2012)
Religion and reason : a new institutionalist perspective -- Religion and change : Oxford and the madrasas of South Asia -- Explaining the stickiness : state-madrasa engagement in South Asia -- Organization of religious hierarchy : competition or cooperation? -- Formation of a preference : why join a madrasa? -- Logic of adaptive preference : Islam and western feminism -- The missing free-rider : religious rewards and collective action -- Exclusionary institutional preference : the logic of jihad -- Informal institutions and development